2013
DOI: 10.1177/0022427813512494
|View full text |Cite
|
Sign up to set email alerts
|

Criminogenic Facilities and Crime across Street Segments in Philadelphia

Abstract: Objectives: Test whether the exposure of street segments to five different potentially criminogenic facilities is positively related to violent, property, or disorder crime counts controlling for sociodemographic context. The geographic extent of the relationship is also explored. Method: Facility exposure is operationalized as total inverse distance from each street segment in Philadelphia, PA, to surrounding facilities within three threshold distances of 400, 800, and 1,200 feet. All distances are measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(54 citation statements)
references
References 92 publications
3
50
0
1
Order By: Relevance
“…For example, for the first statistically significant agglomeration of alcohol outlets, simple assaults clustered within three distance ranges: between 575 and 659 feet from the alcohol outlet agglomeration, between 1500 and 1613 feet from the alcohol outlet agglomeration, and between 2637 and 3061 feet from the alcohol outlet agglomeration . Additionally, Groff and Lockwood (2014) found that bars were associated with violent, property, and disorder crimes within 400 feet of the street segment that contained bars, as well as within 800 feet and 1200 feet away from the street segments that contained bars. Most of these prior studies, however, have grouped all crimes (e.g., Britt et al, 2005) or all violent crimes (e.g., Gorman et al, 2001;Zhu et al, 2004) into one broad category.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for the first statistically significant agglomeration of alcohol outlets, simple assaults clustered within three distance ranges: between 575 and 659 feet from the alcohol outlet agglomeration, between 1500 and 1613 feet from the alcohol outlet agglomeration, and between 2637 and 3061 feet from the alcohol outlet agglomeration . Additionally, Groff and Lockwood (2014) found that bars were associated with violent, property, and disorder crimes within 400 feet of the street segment that contained bars, as well as within 800 feet and 1200 feet away from the street segments that contained bars. Most of these prior studies, however, have grouped all crimes (e.g., Britt et al, 2005) or all violent crimes (e.g., Gorman et al, 2001;Zhu et al, 2004) into one broad category.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…While the census block group is a commonly used unit of analysis in neighborhood level studies of violence, and is better theoretically grounded than the use of census tracts, zip codes, or counties, it contains artificially imposed boundaries that are used to capture neighborhood boundaries. The use of street segments that are comprised of street blocks, or street corners and block faces (e.g., Braga et al, 2011;Groff and Lockwood, 2014;Smith et al, 2000) might better represent natural neighborhood boundaries and reduce the likelihood of pattern obfuscation (Andersen and Malleson, 2011), making it a more appropriate spatial unit of analysis for estimating the association of alcohol outlets and neighborhood robbery occurrences. Fourth, our study does not control for the influence of other retail establishments that might serve as crime attractors (e.g., gas stations, laundromats, pawn shops, check cashing services, vice-related incidents) on neighborhood robbery levels, or directly test for availability of vulnerable targets (e.g., number of intoxicated individuals).…”
Section: Limitationsmentioning
confidence: 99%
“…Transport land uses therefore act as nodes and paths. Groff and Lockwood (2014) report a positive associated between subway stations and violent crime, property crime, and disorder.…”
Section: Description Of Practical Examples Of Gj and Significance To mentioning
confidence: 99%
“…Transit-related land uses have been linked to increased crime risks (Groff and Lockwood 2014;Kondo et al 2016;Ridgeway and MacDonald 2017) and subway stations have been found to attract street robberies (McCord and Ratcliffe 2009). Phillips and Sandler (2015) show how public transport can influence the geographical distribution of crime.…”
Section: Description Of Practical Examples Of Gj and Significance To mentioning
confidence: 99%
“…However, while some studies have found a positive correlation between streets and crime, while others have found either a negative correlation or they found no evidence to link crime with streets. For example, studies by Jochelson (1997) and Groff and Lockwood (2014) both observed that the number of crime incidents accrued on streets or near streets where train stations, bars, subway stations, parks, schools and pubs were located. Yet Ridgeway and MacDonald (2017) examined if there was a link between rail station openings and crime rates in Los Angeles from 1990 to 2012 and found no evidence that these places or the surrounding neighbourhoods affected any change in crime.…”
mentioning
confidence: 99%